Living Sufism and Ecological Ethics: Integrating Spiritual Values and Local Wisdom in Environmental Conservation of Nagari Paninggahan, West Sumatra - Arrasyid Arrasyid; Junizar Suratman; Gazali Gazali; Rido Putra (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
Nagari Paninggahan is well known for preserving Minangkabau traditions that integrate Islamic teachings, customary law, and sustainable natural resource management. This study examines how Sufi values are embedded in local customs and their role in environmental conservation. Employing a qualitative ethnographic approach, data were collected through interviews, observations, and documentation involving community leaders, village officials, and local residents. The findings reveal that traditions such as Lubuk Larangan and Balimau promote ecological ethics by regarding forests, rivers, fisheries, and agricultural ecosystems as sacred trusts (amanah) entrusted by God. This spiritual perspective encourages environmental responsibility, limits resource exploitation, and reinforces sustainable practices. The study concludes that the integration of Sufi spirituality and Minangkabau customary traditions contributes significantly to ecological sustainability while preserving local cultural identity and strengthening community-based environmental stewardship. Contribution: This study provides insight into Sufism's role in fostering environmental awareness, promoting harmony between humans and nature, and maintaining cultural identity.